The control of the liquidity and the Radcliffe Committee - HUME, L.J. (PSL Quarterly Review, 2014)
In “The Control of Liquidity in Italy”, A. Gambino offered an interesting account of factors determining the levels of bank liquidity, money and quasi-money in Italy. In his opening remarks, however, he linked his comments with the Radcliffe Committee’s view that “it is the liquidity of the economy rather than the supply of money that the authorities should seek to affect by their use of monetary measures”. In this brief note, the author argues that this reference to the Radcliffe Committee’s conclusion is not appropriate as it implies a misleading picture of the Committee’s thesis. Moreover, the concept of liquidity used by the Committee is not the same as that explored by Gambino in remainder of his article. JEL: E42, E51, E52